PENGARUH KECERDASAN EMOSIONAL TERHADAP KEMANDIRIANBELAJAR DI SMP NEGERI 6 BINJAI TAHUN PELAJARAN 2019/2020 - Intan Chumairah Pasaribu; Rusydi Ananda Rusydi Ananda; Eka Susanti Eka Susanti (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2021)
Abstract: This study aims to determine whether there is an influence of emotional intelligence on independent learning at SMP Negeri 6 Binjai. This type of research uses quantitative research methods, with correlation techniques and analysis techniques with simple linear regression. The subjects in this study were class VIII students of SMP Negeri 6 Binjai in the 2019/2020 school year, totaling 283 students.Collecting data for the variables of emotional intelligence and learning independence using a questionnaire in the form of a Likert scale. The questionnaire was compiled based on variable indicators and checked by the thesis supervisor, and then tested on students. Based on data analysis, it showed that there was an influence of emotional intelligence on learning independence at SMP Negeri 6 Binjai. The conclusion is proven from the analysis of the calculation of the hypothesis test which shows that the calculated r is greater than rtable, which is 0.702 > 0.232 which can be accepted at a significant level of 5%.Keywords: Emotional intelligence, independent learning